Examining Neanderthal and carnivore occupations of Teixoneres Cave (Moià, Barcelona, Spain) using archaeostratigraphic and intra-site spatial analysis - Zilio, Leandro (2021)
Teixoneres Cave (Moià, Barcelona, Spain) is a reference site for Middle Palaeolithic studies of the Iberian Peninsula. The cave preserves an extensive stratigraphic sequence made up of eight units, which is presented in depth in this work. The main goal of this study is to undertake an initial spatial examination of Unit III, formed during Marine Isotope Stage 3, with the aim of understanding spatial organization and past activities developed by Neanderthals and carnivores (bears, hyenas and smaller carnivores). The total sample analysed includes 38,244 archaeological items and 5888 limestone blocks. The application of GIS tools allows us to clearly distinguish three geologically-defined stratigraphic subunits. Unit III has been previously interpreted as a palimpsest resulting from alternating occupation of the cave by human groups and carnivores. The distribution study shows that faunal specimens, lithic artefacts, hearths and charcoal fragments are significantly concentrated at the entrance of the cave where, it is inferred, hominins carried out different activities, while carnivores preferred the sheltered zones in the inner areas of the cave. The results obtained reveal a spatial pattern characterized by fire use related zones, and show that the site was occupied by Neanderthals in a similar and consistent way throughout the ˃ 7000 years range covered by the analysed subunits. This spatial pattern is interpreted as resulting from repeated short-term human occupations.